Case report: Primary pulmonary low grade fibromyxoid sarcoma progressing to dedifferentiation: probably due to TP53 driver mutation - Zhang, Jiawen; Fang, Haisheng; Zhu, Xiaomei; Yao, Chenchen; Fan, Qinhe; Gong, Qixing (Frontiers in Oncology, 2024)
Low Grade Fibromyxoid Sarcoma (LGFMS), a rare entity characterized by bland histologic features, typically affects deep soft tissues of the trunk and lower extremities.Rare cases have been reported arising from the viscera and few demonstrating morphology of high-grade dedifferentiation. Here we report a 39-year-old Chinese woman presenting with primary lung LGFMS, which metastasized to the pancreas five years after diagnosis and then relapsed ten years later as a mediastinum mass.Microscopically, the lung and pancreatic lumps shared similar classical features ofLGFMS, composed of bland spindle-shaped cells with low mitotic activity. However, the mediastinal mass had dedifferentiated morphology of dense sheets of round and epithelioid cells with high degree of nuclear pleomorphism and brisk mitosis.Molecular studies showed both classical and dedifferentiated areas had FUS::CREB3L2 rearrangement. However, the mediastinal dedifferentiated area presented with extra H193Y mutation of the TP53. Moreover, the mediastinal tumor displayed a strong and diffuse pattern of p53 expression immunohistochemically, but the primary lung and secondary pancreatic masses did not. Thus, we diagnosed the mediastinal mass as dedifferentiated LGFMS and proposed that TP53 mutation was probably the driver gene alteration in the process, which, to the best of our knowledge, has not been reported in the existing literature.